Implementasi Pembelajaran Tahfiz dalam Mengembangakan Kongnitif pada Anak 5-6 Tahun di RA Al-Fajar Medan Denai - Apriliana Arief Tiara Putri; Hadis Purba; Sri Wahyuni (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2024)
In accordance with the formulation of the problem, this study aims to determine: 1) the implementation of tahfidz learning in developing cognitive in children aged 5-6 years at RA Al-Fajar Medan Denai. 2) Supporting and inhibiting factors in the implementation of tahfidz learning in developing cognitive in children aged 5-6 years at RA Al-Fajar Medan Denai This study uses a qualitative research method involving 2 teachers in group B and the principal, data collected through observation and interviews. The results of this study indicate that: 1) The implementation of tahfidz learning in improving the cognitive development of children aged 5-6 years at RA Al-Fajar Medan Denai is carried out by designing a clear learning curriculum and integrating tahfidz learning in it, introducing basic concepts of the Qur'an in a gradual and interesting manner, choosing the right learning method according to learning objectives, providing regular and structured memorization exercises, and providing positive feedback and reinforcement to children when they succeed in memorizing verses. 2) Supporting and inhibiting factors in the implementation of tahfidz learning in developing cognitive in children aged 5-6 years at RA Al-Fajar Medan Denai, namely the supporting factors are support from school management, teacher competence in learning, cooperation between teachers and parents, a conducive environment. While the inhibiting factors are the limited learning time available at school, the diverse initial abilities of children, lack of monitoring and evaluation of children's tahfidz learning.